Air Waves Effect on Sea Bed Logging for Shallow Water Application - Daud, Hanita (Scopus.com, 2010)
Sea bed logging (SBL) is a technique for finding resistive layers, which can be hydrocarbon reservoirs in the subsurface using marine controlled source electromagnetic (CSEM) survey. In CSEM, a mobile horizontal electric dipole (HED) source transmits low frequency EM signal which is towed over an array of seafloor receivers measuring the electric and/or magnetic field. This EM signal induces an airwave along the air/sea surface that interferes with the signal that comes from the subsurface and this airwave will start dominating at larger offsets. Airwave is actually the energy that propagates from the source through the atmosphere to the receiver on the seabed. Airwave component is problematic in shallow water because it is less attenuated during its up and down propagation compared to deeper water. This paper will present the air wave amplitude verses water depth relationship. Using the simulator that has been developed using MATLAB software we will set up a forward model that contains air, sea water, sediments and hydrocarbon reservoir with their resistivity values respectively. Sea water depth will be varied starting from 250m and is incremented every 250m until the airwaves signal captured by the receiver becomes insignificant or approaching to zero. From this simulation we shall find the water depth on which airwave has less effect on the desired forward model.